Predictive Analysis of Structural Damage in Submerged Structures: A Case Study Approach Using Machine Learning - Alexandre Brás dos Santos; Hugo Mesquita Vasconcelos; Tiago M. R. M. Domingues; Pedro J. S. C. P. Sousa; Susana Dias; Rogério F. F. Lopes; Marco L. P. Parente; Mário Tomé; Adélio M. S. Cavadas; Pedro M. G. P. Moreira (Fluids)
This study focuses on the development of a machine learning (ML) model to elaborate on predictions of structural damage in submerged structures due to ocean states and subsequently compares it to a real-life case of a 6-month experiment with a benthic lander bearing a multitude of sensors. The ML model uses wave parameters such as height, period and direction as input layers, which describe the ocean conditions, and strains in selected points of the lander structure as output layers. To streamline the dataset generation, a simplified approach was adopted, integrating analytical formulations based on Morison equations and numerical simulations through the Finite Element Method (FEM) of the designed lander. Subsequent validation involved Fluid–Structure Interaction (FSI) simulations, using a 2D Computational Fluid Dynamics (CFD)-based numerical wave tank of the entire ocean depth to access velocity profiles, and a restricted 3D CFD model incorporating the lander structure. A case study was conducted to empirically validate the simulated ML model, with the design and deployment of a benthic lander at 30 m depth. The lander was monitored using electrical and optical strain gauges. The strains measured during the testing period will provide empirical validation and may be used for extensive training of a more reliable model.